Direction of Arrival Estimation with Microphone Arrays Using SRP-PHAT and Neural Networks - Díaz-Guerra Aparicio, David; Beltrán Blázquez, José Ramón (Jornada de Jóvenes Investigadores del I3A, 2018)
The Steered Response Power with phase transform (SRP-PHAT) is one of the most employed techniques for Direction of Arrival (DOA) estimation with microphone arrays, but its computational complexity grows when the search space increases. To solve this issue, we propose the use of Neural Networks (NN) to obtain the DOA from low-resolution SRP-PHAT power maps.